Analisis Kompetensi Awak Kapal Penyeberangan di Kawasan Timur Indonesia - Oktavera Sulistiana; Subehana Rachman (Syntax Corporation, 2023)
Shipping safety has always been an interesting topic and a focus for all stack holders in the Indonesian sea, river, lake and crossing transportation community. One of the factors that play an important role in supporting shipping safety is the competence of the crew. The purpose of this study is to provide an overview of the level of competence of crossing crews in Eastern Indonesia in terms of the fulfillment of CMT and CMHBT Certificates as required by STCW Chapter V Regulation V / 2. This research is a type of Normative Research carried out for approximately 8 months on ships operating on the Sheet-Padangbai, Gilimanuk-Ketapang and Bajoe-Kolaka trajectories with a Judgement Sampling system. The data used is in the form of qualitative data based on the results of a survey of the completeness of CMT and CMHBT certificates from the Crossing Ship Crew. The results of this study found that the competence of Crossing Crew in Eastern Indonesia in terms of compliance with CMT and CMHBT Certificates used as research variables was above 80% of the number of crew surveyed. However, the study also found that there was a misperception regarding the obligation to fulfill the CMT certificate required for all crossing crew and the CMHBT certificate which should only be required for the Skipper, Head of the Engine Room, Mualim I, Driver II and other personnel who fit the Muster List on board passenger ships and Roro-passengers are responsible for passenger safety in emergency situations, which in this case is the officer of the ship. In fact, in the field, CMHBT certificates have also been fulfilled by crew members who are not officers. This does not meet the efficiency aspect in the application or shipping safety.